Pengaruh Struktur Kepemilikan dan Ukuran Perusahaan terhadap Nilai Perusahaan - Rachmawati, Restika Okta; Suzan, Leny (Owner : Riset dan Jurnal Akuntansi, 2024)
For investors, company value is very significant cause it shows the value of investment in the business. For investors, enterprise value identifies the potential for profit and adequate returns on their investment. In this investigation, we'll find out the simultaneous also partial impact of ownership structure also company size on firm value. The survei population also sample consisted of energy sector businesses that were written on the IDX among 2018-2021. A sample of 44 was collected for this research using purposive sampling, it served to gather data on 11 organizations over a 4 year observation period. The E-Views 12 programme is used in this study's quantitative research approach to conduct simultaneous and partial testing on descriptive analysis and panel data regression. Ownership structure and business size are examples of independent factors that have an influence on firm value which are the dependent variables. The survei results show that managerial, institutional ownership also company size simultaneously effect the company value of energy companies written on the IDX in 2018-2021. In energy businesses written on the IDX among 2018–2021, management ownership has a somewhat favourable impact on company valuation, whilst institutional ownership and company size have no bearing. The Adjusted R-Square score of 49.31% demonstrates the limits of this study. The suggestion for companies is to continue to increase company value by displaying the size of share ownership which can influence company value, especially institutional ownership and company size.